2019
DOI: 10.1101/857367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive ethnolinguistic diversity in Vietnam reflects multiple sources of genetic diversity

Abstract: AbstractVietnam features extensive ethnolinguistic diversity and occupies a key position in Mainland Southeast Asia (MSEA). Yet, the genetic diversity of Vietnam remains relatively unexplored, especially with genome-wide data, because previous studies have focused mainly on the majority Kinh group. Here we analyze newly-generated genome-wide SNP data for the Kinh and 21 additional ethnic groups in Vietnam, encompassing all five major language families in MSEA. In addition to an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…S7B). Previous research showed that the paternal lineages observed in the Liangzhu populations from the Yangtze River Delta were mostly O1a-M119 and in the Taiwan Hanben individuals were mostly O1a1 sublineages (Li et al 2007;, and rice farmers carrying O1a-M119 in the YZRB were likely to be the direct ancestors of modern TK and AN speakers, they migrated southward along the southeast coast of China to Southeast/Southwest China and mainland Southeast Asia (Liu et al 2020;. We observed that O1a1a1b was found at the highest frequency in Hainan, especially in Li people, and its haplogroup frequency showed a general south-to-north decline, suggesting that Li-related ancestors made significant contributions to other southern Chinese populations (Fig.…”
Section: Early Asian Paternal Lineages Left Traces Mainly In the Tibe...mentioning
confidence: 97%
“…S7B). Previous research showed that the paternal lineages observed in the Liangzhu populations from the Yangtze River Delta were mostly O1a-M119 and in the Taiwan Hanben individuals were mostly O1a1 sublineages (Li et al 2007;, and rice farmers carrying O1a-M119 in the YZRB were likely to be the direct ancestors of modern TK and AN speakers, they migrated southward along the southeast coast of China to Southeast/Southwest China and mainland Southeast Asia (Liu et al 2020;. We observed that O1a1a1b was found at the highest frequency in Hainan, especially in Li people, and its haplogroup frequency showed a general south-to-north decline, suggesting that Li-related ancestors made significant contributions to other southern Chinese populations (Fig.…”
Section: Early Asian Paternal Lineages Left Traces Mainly In the Tibe...mentioning
confidence: 97%
“…The linguistic survey has found that the Tai-Kadai language was widely distributed in Southeast Asia, including Zhuang-Dai, Dong-Shui, Li, and Ge-Yang language sub-branches (Edmondson, 1988;Liang and Zhang, 1996;Edmondson, 1997;Kutanan et al, 2019;Liu et al, 2020;Kutanan et al, 2021). Linguistic findings showed that Maonan is a subgroup of the Dong-Shui language, mainly distributed in Guizhou, Guangdong, and Guangxi provinces (Lu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Linguistic findings showed that Maonan is a subgroup of the Dong-Shui language, mainly distributed in Guizhou, Guangdong, and Guangxi provinces (Lu, 2008). Historians hold the opinion that Tai-Kadai people in South China are one of the indigenous population with a long history (Wang, 2004;Huang, 2016;Zhang, 2016), which is also evidenced via the linguistic documents and ancient DNA evidence (Edmondson, 1988;Liang and Zhang, 1996;Lipson et al, 2018;McColl et al, 2018;Liu et al, 2020;Kutanan et al, 2021). Direct documents from historic materials showed that the Maonan ethnic group is related to the modern Southern Chinese indigenous ethnic groups such as Bouyei, Mulam, and Gelao (Wang, 2004;Huang, 2016).However, the historical records for the origin of Maonan and the records of local Chronicles inscriptions and genealogies are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past hundreds of years, the TK people gradually migrated southward, driven by various cultural, political, economic, environmental and other relevant factors, and became the majority inhabitants of Southeast Asia [8,13,14]. In light of the complex population history of TK-speaking groups and the important role played in the peopling of East and Southeast Asia, the analyses of genetic variations in TK-speaking populations have been conducted in several studies using different sets of autosomal [15][16][17], X-chromosomal [18,19], Y-chromosomal [20,21], mitochondrial [13,14,[21][22][23] and genome-wide [7,24] markers. Previous studies showed that the Proto-languages of TK and AN might be related [25], and TK people from Thailand are related to AN speakers based on mitogenome sequences [14].…”
Section: Introductionmentioning
confidence: 99%